Memoria e storia nelle narrazioni postcoloniali di Regina di fiori e di perle di Gabriella Ghermandi e Memorie di una principessa etiope di Martha Nasibù - Kornacka, Barbara (Romanica Silesiana, 2020)
The aim of thise paper is to show how the setting out of the narrative voice determines the historical discourse. The analysis of the narrative voice leads to some considerations about memory and to the examination of recollection in these two novels. That, in turn, allows an exploration of the way in which the historical discourse is constructed. In those cases where the voice in the historical discourse is given to subaltern subjects, they contribute to a more plural history.